3D-printable aerogel-incorporated concrete: Anisotropy influence on physical, mechanical, and thermal insulation properties. (14th March 2022) - Ma, Guowei; A, Ruhan; Xie, Panpan; Pan, Zhu; Wang, Li; Hower, James C.
Highlights: To achieve the desired printability, the optimal replacement range for silica sand by aerogel in a cementitious mixture is 0–20% by volume. The thermal conductivities of the SC and 3D printed specimens ranked in the order of 3DCP-X > SC > 3DCP-Y > 3DCP-Z, irrespective of aerogel content. The weak bonding interfaces between adjacent filaments produce gaps, providing channels for heat to transfer in specimens 3DCP-X. Under the same thermal and mechanical requirements, walls fabricated by AG-incorporated concrete are 7-cm thinner than traditional concrete walls. Abstract: This study investigated the properties of fresh and hardened aerogel (AG)-incorporated concrete suitable for 3D concrete printing. After trial and error, it was found, that to achieve the desired printability, the optimal replacement range for silica sand by aerogel in a cementitious mixture is 0–20% by volume. The physical, mechanical, and thermal insulation properties of hardened concrete in three directions were studied, and the influence of anisotropy on these properties was investigated. The results showed that irrespective of the aerogel content, the compressive strength of the cast specimens (avg. 24.90 MPa in A20) was slightly higher than those of the 3D printed specimens, 3DCP-X (avg. 23.63 MPa in A20), 3DCP-Y (avg. 20.77 MPa in A20), and 3DCP-Z (avg. 20.40 MPa in A20). The thermal conductivity of the cast and printed specimens decreased gradually with an increase in the aerogel content. Relative to that of the cast specimens (0.330 W/(m·K) in A20), the thermal conductivity of specimens 3DCP-X (0.405 W/(m·K) in A20) was slightly higher, while those of 3DCP-Y (0.320 W/(m·K) in A20) and 3DCP-Z (0.306 W/(m·K) in A20) were lower. A thermal insulation wall (400 mm × 200 mm × 600 mm) with hollow structures was printed using the AG-incorporated concrete. To satisfy the same thermal and mechanical requirements, walls fabricated using AG-incorporated concrete can be 7 cm thinner than traditional concrete walls. The mechanism for the heat transfer of AG-incorporated concrete in three directions was examined as well.